2008
DOI: 10.7863/jum.2008.27.8.1235
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Diagnosis of a Radiographically Undiagnosed Hook of the Hamate Fracture

Abstract: Abbreviations CT, computed tomography; HH, hook of the hamate Case ReportA 54-year-old right-handed woman was referred by a hand surgeon because of local pain in the ulnar aspect of the right wrist radiating down into the fourth and fifth fingers. She had a fall on both wrists 4 months previously. Standard anteroposterior and lateral radiographs obtained after the accident showed a displaced fracture of the left distal radius but no traumatic lesions of the right wrist. She was successfully treated by osteosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
(24 reference statements)
0
15
0
2
Order By: Relevance
“…This case highlights some of the problems encountered with traditional x-ray views, and the need to consider oblique views as either standard procedure or as an adjunct where clinical suspicion remains high even in the presence of normal x-rays. This point remains valid even given the increasing use and availability of other forms of radiological investigation [6-9]. …”
Section: Discussionmentioning
confidence: 96%
“…This case highlights some of the problems encountered with traditional x-ray views, and the need to consider oblique views as either standard procedure or as an adjunct where clinical suspicion remains high even in the presence of normal x-rays. This point remains valid even given the increasing use and availability of other forms of radiological investigation [6-9]. …”
Section: Discussionmentioning
confidence: 96%
“…The normal periosteum, depending on its thickness, can sometime difficult to assess by sonography. Due to its tomographic capabilities, sonography can show acute fractures that are difficult to image on radiography and can show a variety of stress fractures . A recent study on sonographic and radiographic capabilities in the early detection of metatarsal stress fractures showed that sonography had sensitivity of 83% and specificity of 76% (correlated with MRI) and that sonography was more sensitive than standard radiography for this purpose …”
Section: Discussionmentioning
confidence: 99%
“…Les fractures du hamatum (os crochu) sont rares, en particulier celles intéressant le corps, et ne constituent que 2 % de toutes les fractures du carpe [1,2]. Elles ne sont pas souvent évoquées comme diagnostic différentiel devant un traumatisme carpien et peuvent passer inaperçues.…”
Section: Discussionunclassified
“…La TDM reste l'examen de choix dans le diagnostic de ce type de fracture en précisant les traits fracturaires et le nombre de fragments ainsi que leur possible déplacement [2]. Dans une étude faite sur 18 mains de cadavres, la TDM avait une sensibilité de 100 % et une spécificité de 94,4 % alors que la radiographie conventionnelle a montré une sensibilité de 72,2 % et une spécificité de 88,8 % [5].…”
Section: Discussionunclassified